2002
DOI: 10.1046/j.1365-2141.2002.03878.x
|View full text |Cite
|
Sign up to set email alerts
|

A family of textilinin genes, two of which encode proteins with antihaemorrhagic properties

Abstract: Summary. Two peptides, textilinins 1 and 2, isolated from the venom of the Australian common brown snake, Pseudonaja textilis textilis, are effective in preventing blood loss. To further investigate the potential of textilinins as antihaemorrhagic agents, we cloned cDNAs encoding these proteins. The isolated full-length cDNA (430 bp in size) was shown to code for a 59 amino acid protein, corresponding in size to the native peptide, plus an additional 24 amino acid propeptide. Six such cDNAs were identified, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
43
0
2
Order By: Relevance
“…Masci et al (9) identified and characterized serine protease inhibitors from the venom, named them textilinins, and showed that they significantly reduce bleeding in an animal model. More recently, six isoforms of textilinin have been identified in P. textilis venom gland-derived cDNA (10). A prothrombin-activating complex was identified by Masci et al (11) and was found to comprise a large proportion of the venom.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Masci et al (9) identified and characterized serine protease inhibitors from the venom, named them textilinins, and showed that they significantly reduce bleeding in an animal model. More recently, six isoforms of textilinin have been identified in P. textilis venom gland-derived cDNA (10). A prothrombin-activating complex was identified by Masci et al (11) and was found to comprise a large proportion of the venom.…”
mentioning
confidence: 98%
“…These include postsynaptic ␣-neurotoxins (2-4), the presynaptic neurotoxin textilotoxin (5-7), phospholipase A 2 s (PLA 2 s) 1 (6,8); serine protease inhibitors (9,10), and a prothrombin activator (11,12). Fry (13) has written a comprehensive review on the properties of venom components from Australian elapids.…”
mentioning
confidence: 99%
“…To date a number of BPTI-like superfamily serine protease inhibitors from Viperidae and Elapidae venoms have been purified or characterized [3,4,12,13,15,16,18,19,25,26,[29][30][31][32][33][34]35,36,39]. In this paper, one chymotrypsin inhibitor, BBPTI-1, was purified to homogeneity from the venom of Burmese Daboia russelli siamensis by gel filtration, cation exchange and reversed phase chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…The 24-amino-acid propeptide sequence is hydrophobic, which suggests that it facilitates secretion of the protein prior to cleavage. Of the six textilinins that have been characterized, only Txln-1 and Txln-2 are effective in reducing blood loss in the mouse-tail model (Filippovich et al, 2002). A sequence alignment of the textilinins shows that arginine in position 17 (the residue that binds in the P1 pocket in serine proteases) is common to Txln-1 and Txln-2, while the other four textilinins have an asparagine, lysine, glutamate or aspartate in this position.…”
Section: Introductionmentioning
confidence: 99%
“…Txln-1 is an acidic molecule with a pI of 4.4 (Filippovich et al, 2002), while aprotinin is basic with a pI of 8.9 (Gebhard et al, 1986). The reason for this difference is that there are 11 negatively charged and seven positively charged amino acids in Txln-1, while in aprotinin there are only four negatively charged and ten positively charged amino acids.…”
Section: Introductionmentioning
confidence: 99%